IMPLEMENTASI PENYELENGGARAAN KETERTIBAN UMUM DAN KETENTRAMAN MASYARAKAT PADA DINAS SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN SIDENRENG RAPPANG - Marwah Marwah; Erfina Erfina; Hariyanti Hamid (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
This study aims to determine the implementation of the Regional Regulation No. Enforcement Policy. 8 of 2012 concerning the implementation of public order and public order at the Sidenreng Rappang District Police Service Unit and Fire Service and factors that hinder the implementation of the policy on the Enforcement of Regional Regulation No. 8 of 2012 concerning the implementation of public order and public order at the Service of the Civil Service Police Unit and the Fire Department of Sidenreng Rappang Regency using qualitative descriptive research. The results showed that the implementation of the Local Regulation No. Enforcement Policy. 8 of 2012 concerning the implementation of public order and public order at the Sidenreng Rappang District Police and Fire Service Offices have been well implemented, seen from the aspects of standards and policy targets, resources, communication between organizations and strengthening activities, characteristics of implementing agencies, social conditions. economics and politics and the disposition of implementors. While the factors that hinder the implementation of the policy on the Enforcement of Regional Regulation No. 8 of 2012 concerning the implementation of public order and public order at the Service of the Civil Service Police Unit and the Fire Service of Sidenreng Rappang Regency, among others, institutionally, human resources, work networks and an environment that is not yet conducive.